PRESCHOOL EDUCATIONAL ORGANIZATION AND ESTABLISHMENT OF PUPPET THEATER IN SCHOOLS (Conference Zone, 2021)
It is a well-known fact that human beings possess and create beauty throughout history. Beauty is part of the cultural-historical experience. Its objective existence leads to the development of the theory of aesthetic education, active ways of imparting aesthetic experience to the younger generation in a purposeful and regular manner, and thus ensuring its aesthetic development. In this case, the main means of mastering the culture of aesthetic education is upbringing and education. One of the tools of aesthetic education is puppet theater. Its extremely strong influence is due to its simplicity, extraordinary enthusiasm and puppetry (playfulness), as well as the integral integration of such components as artistic speech, music, singing, dancing, fine arts. is clearly visible to the human eye.